As A Means of Shaping the Spiritual and Ethical Culture of Students in the Tradition of Uzbek National Art (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Attention to all stages of the system of continuing education in the country, including its pre-school education, is growing day by day. President of the Republic of Uzbekistan Sh. It is important to radically improve the level of preparation of children for school education in the implementation of the Resolution of Mirziyoyev dated December 29, 2016 No PQ-2707 "On measures to further improve the system of preschool education in 2017-2021" defined as a task. As we have already mentioned, the effective functioning of the stages of continuing education depends to a large extent on the quality of preschool education, during which the child's outlook and imagination develop and, most importantly, the necessary foundation is laid for his formation as a person.